Message from the Chief Editor - Editor, Chief (Journal of Technical Education and Training, 2015)
Welcome to all our readers to the 2015 June issue of JTET.  In this issue we are proud to present to our readers six new articles from our international contributors who have generously shared their research findings on the various aspects of TVET.  The first article by Odo discusses the critical importance of making available the right information in ensuring effective career decision making and career development for TVET students. It highlights the challenges faced by students in making the right choices and the need for adequate and accurate information for their decision making and career development goals. The second article by Chinedu and Oladiran highlights another role of TVET that is rarely discussed, i.e.,  its specific role in promoting better peace and security of a nation.  National security is indeed an important goal to achieve if any progress is to be achieved by any nation.  The third article by Ahmad, Nordin, Ali and Nabil looks at how a teaching method that is often associated with science teaching can be successfully applied to the teaching and learning in TVET. Although the example is set within the teaching and learning of an automotive course, courses of similar nature in TVET would equally benefit.  The rest of the articles, fourth and fifth are all focussing on ICT integration in TVET, from planning to implementations. Thus, while the paper by Hadihedayati and Laanpere raises concerns about providing ICT facilities according to actual needs of the population it is supposed to serve – in this case Afghanistan - the paper by Analisa provides empirical evidence on the worthiness of ICT in promoting meaningful learning in TVET. Last but not least, the paper by Mehar and Nebhnani discusses how specific application can be exploited to provide effective presentations that would support learning of abstract concepts in TVET such as those found in electrical and electronic technology.  To all our authors, thank you for making this issue possible. To our reviewers, thank you for helping us in ensuring JTET achieve the high quality that it aims for. We hope everyone; from authors to reviewers will continue to give their strong support so that we can continue to provide the knowledge sharing that is made possible through research publications by global TVET practitioners and researchers.  Prof. Dr. Maizam Alias